ACTR-06. INITIAL RESULTS OF A PHASE I STUDY OF PROCASPASE ACTIVATING CCOMPOUND-1 (PAC-1) IN COMBINATION WITH TEMOZOLOMIDE FOR RECURRENT MALIGNANT GLIOMA. (5th November 2018) - Nicholas, Martin; Holdhoff, Matthias; Peterson, Richard; Danciu, Oana; Wefel, Jeffrey; Tarasow, Ted; Hergenrother, Paul J; Dudek, Arkadiussz
Abstract: Disruption of the intrinsic and extrinsic apoptotic pathways is a hallmark of neoplasia. Conversion of procaspase-3 to caspase-3 is a key reaction, as both pathways converge at this point. Procaspase activating compound -1 (PAC-1) catalyzes conversion of procaspase-3 to caspase-3 and induces apoptosis in tumor cells. Glioblastoma (GBM) is among the tumors that have high concentrations of procaspase-3 and low levels of caspase-3. PAC-1 has anti-tumor activity in several glioma cell lines in vitro . PAC-1 crosses the blood brain barrier and its addition to alkylating chemotherapy augments anti-tumor responses in in vivo rodent models and spontaneous canine gliomas. Taken together, these findings suggest PAC-1's potential in glioma therapy. This dose-escalation phase I study to assesses the maximum tolerated dose (MTD) of PAC-1 administered daily for 21 days with TMZ, 150 mg/m 2 for 5 days of each 28 day cycle in subjects with recurrent anaplastic astrocytoma (AA) or GBM. RANO criteria are used to assess response. A modified Fibonacci 3 + 3 design is used, expanding to 9 subjects at the MTD. Pharmacokinetics (PK) is assessed in each subject during cycle one. Secondary endpoints include pharmacodynamics and correlation of activity with procaspase-3 levels in tumor tissue. Neurologic toxicity, including cognitive function, is closely monitored throughout the trial. 6 subjects (all GBM) enrolled at the first dose level, 375 mg PAC-1/day. The PAC-1cycles administered ranged from 1–6 (mean = 3.2). All subjects left the study due to tumor progression. The best radiographic response was stable disease. The first cohort was expanded from 3 to 6 due to CTCAE grade 4 hepatotoxicity that resolved with dose reductions in both study drugs. An update of toxicity data and results of PK and tumor procaspase levels will be discussed.